Ladies’ and Misses’ Slip-Over Waist sewing pattern - McCall Pattern Company (1912)
Sewing pattern envelope for a women's tunic. In 1870, Scottish immigrant James McCall began designing and printing his own line of sewing patterns. To advertise his patterns, McCall founded a four-page fashion journal entitled The Queen: Illustrating McCall's Bazaar Glove-Fitting Patterns. By 1893, the publication remained primarily a vehicle to sell McCall's sewing patterns, however, it had begun to also include articles on children's issues, health, beauty, homemaking and handiwork information, and foreign travel. In time, the magazine's name would be shortened to McCall's, and remained popular for much of the 20th century. For many years, information on McCall's patterns filled an average of 20 percent of the magazine's pages. McCall's was the first pattern company to introduce printed patterns (printed directions on their patterns rather than perforations) in 1919. McCall's patterns were also pioneers in color-printed patterns starting in the mid-1930s.
Keywords: Sewing; Sewing--Equipment and supplies; Clothing and dress